Transcriptome-wide identification and characterization of the Sox gene family and microsatellites for Corbicula fluminea - Chuankun Zhu; Lei Zhang; Huaiyu Ding; Zhengjun Pan (PeerJ, 2019)
The Asian clam, Corbicula fluminea, is a commonly consumed small freshwater bivalve in East Asia. However, available genetic information of this clam is still limited. In this study, the transcriptome of female C. fluminea was sequenced using the Illumina HiSeq 2500 platform. A total of 89,563 unigenes were assembled with an average length of 859 bp, and 36.7% of them were successfully annotated. Six members of Sox gene family namely SoxB1, SoxB2, SoxC, SoxD, SoxE and SoxF were identified. Based on these genes, the divergence time of C. fluminea was estimated to be around  476 million years ago. Furthermore, a total of 3,117 microsatellites were detected with a distribution density of 1:12,960 bp. Fifty of these microsatellites were randomly selected for validation, and 45 of them were successfully amplified with 31 polymorphic ones. The data obtained in this study will provide useful information for future genetic and genomic studies in C. fluminea.